Effects of Exogenous Acetate Load on Hepatic Acetate Metabolism in Lactating and Non Lactating Sheep - Bugi Rustamadji (Faculty of Animal Science, Universitas Gadjah Mada, 1997)
Artikel dalam bentuk PDF